Pengembangan Wisata Pesisir Berkelanjutan di Gampong Beureunut Melalui Konsep Minapolitan - Agussaini, Halis; Zainuddin, Zainuddin (Yayasan Kawanad, 2025)
Beureunut Village, Seulimeum Subdistrict, Aceh Besar Regency is a coastal area with significant potential for fisheries and tourism, yet remains underutilized. This community service program aims to support coastal tourism development based on the minapolitan concept as a strategy to improve community welfare. Activities were conducted using a participatory approach, beginning with mapping the village's potential, identifying issues, and developing an integrated concept for fisheries and tourism-based area development. Findings reveal that Beureunut Village possesses geographical advantages, biological richness (including eel habitats), and potential for eco-tourism rooted in local culture. Nevertheless, challenges including infrastructure limitations, institutional constraints, and market access remain major obstacles. The program produced a development plan for a coastal tourism-minapolitan area that integrates eco-tourism functions, a fisheries hub, and the empowerment of SMEs based on marine products. Implementation of the concept is expected to boost the local economy and establish a sustainable model for coastal village development.